Sensorless Rapidly Varying Rotor Speed Control of BLDC Motor through Fast Commutation Error Correction Method (International Journal of Scientific Research in Science and Technology, 2025)
The sensorless control of a BLDC (Brushless DC) motor can be challenging due to the rapidly varying rotor speed, which can result in errors in the commutation process. In this context, a fast commutation error correction method is proposed to overcome this issue. The proposed method utilizes an estimation of the rotor position based on the changing voltage when the device is placed in a magnetic field of the motor, which is measured by a Hall effect sensor. The measured voltage is used to calculate the rotor position. To implement the proposed method, a current controlled pulse width modulation (PWM) technique which uses a PID (Proportional Integral Derivative) controller to adjust the commutation angle. The performance of the system is evaluated through simulation and experimental studies, which demonstrate its ability to achieve accurate sensorless control of a BLDC motor, even under rapidly varying rotor speed conditions. Overall, the fast commutation error correction method provides a viable solution for achieving sensorless control of BLDC motors under challenging conditions, such as those encountered in high-speed applications.